Comparison of the Effect of Peer-led Education and Education by the Healthcare Personnel on Awareness, Attitude and Performance of Lettered People toward Organ Donation - M Mohammadpour (Babol University of Medical Sciences, 2019)
BACKGROUND AND OBJECTIVE: Lack of donation is one of the major limitations of organ transplantation. Promoting organ donation requires increased awareness and creation of a positive attitude through training in specific ways. The purpose of this study was to compare the effect of peer-led education and education by healthcare personnel on awareness, attitude and performance of lettered people in regard with organ donation. METHODS: This case-control clinical trial was performed on 120 lettered people who were randomly assigned to three groups of 40, including peer-led, healthcare personnel and control groups. The two intervention groups underwent training sessions. Before and after the intervention, the data were collected and compared using questionnaires in three groups in three areas of awareness, attitude and performance. FINDINGS: Most of the lettered people (58.33%) were female. 61.66% had a bachelor's degree and 60.83% were teachers at elementary school. There was a significant difference in the mean scores of awareness, attitude and performance toward organ donation in the two intervention groups before the intervention (in peer-led group were 11.52 ± 2.12, 92.05 ± 10.24, and 1.87 ± 1.42 and in healthcare group were 11.30 ± 3.00, 90.73 ± 10.92, and 1.38 ± 1.29, respectively) and after the intervention (in peer-led group were 15.47 ± 1.13, 98.78 ± 5.70, and 3.53 ± 0.50 and in healthcare group were 15.13 ± 1.49, 96.95 ± 5.52, and 3.05 ± 0.81, respectively) ( P < 0.05). The mean score of attitude and performance of the lettered people in the peer-led group was significantly higher than the other groups (P < 0.05). CONCLUSION: The results of the study showed that peer-led education is a more effective method than education by healthcare personnel to promote and institutionalize organ donation.